Sativex® in multiple sclerosis spasticity: a cost–effectiveness model. (August 2012) - Slof, John; Gras, Adrien
Background: Multiple sclerosis (MS) is a chronic, progressive disease that carries a high socioeconomic burden. Spasticity (rigidity and spasms) is common in MS and a key contributor to MS-related disability.Objectives: This study evaluated the cost–effectiveness of Sativex®, a 9-d-tetrahydrocannabinol/cannabidiol-based oromucosal spray that acts as an endocannabinoid system modulator. Sativex was recently approved for the management of resistant MS spasticity as add-on medication.Methods: A Markov model-based analysis was performed over a 5-year horizon from a German and Spanish healthcare payer perspective. The incremental cost of Sativex was low compared with current spasticity treatments, and provided a quality-adjusted life-year gain over the current standard of care.Results: The base-case incremental cost–effectiveness ratio for Sativex was estimated at €11, 214/quality-adjusted life-year in Germany, while the drug was the dominant option in Spain, providing savings of €3496/patient over a 5-year period (year of costing: 2010). This was seen because the lower severity of spasticity in patients who had improved led to reduced resource consumption (e.g., physiotherapy and medications).Conclusion: Despite having a relatively high acquisition cost, Sativex was shown to be a cost–effective treatment option for patients with MS-related spasticity.